Outdoor Learning Activities in Early Childhood Education: Exploring Benefits and Challenges Through Bibliometric Analysis - Nice Maylani Asril; Ni Wayan Surya Mahayanti; Ni Komang Arie Suwastini; I Wayan Artanayasa; Yukiko Masumoto; Fumiko Kagiura (Faculty of Sport and Health Sciences, 2024)
Despite the growing recognition of positive effects on children's physical, cognitive, social and emotional development through outdoor learning within early childhood education (ECE), these practices are inconsistently integrated into ECE curricula. Current study analyses bibliometric research to explore the trend in fitness training and highlights pertinent authors who conducted valuable research on this issue. Through DimensionAI system, 43 publications were found using “outdoor learning” AND